1979
DOI: 10.1136/sti.55.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Growth and effect of chlamydiae in human and bovine oviduct organ cultures

Abstract: SUMMARY Organ cultures of 10 Fallopian tubes were inoculated with a genital strain of Chlamydia trachomatis and seven were infected. Infection was enhanced by centrifuging the organisms on to the tissues, larger numbers of organisms being reisolated from the tissues after this procedure. There was evidence of chlamydial multiplication because the number of organisms which were recovered from the tissues three to five days after inoculation had increased. Recovery was rare, however, after the sixth day, thus su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
2
5
0
1
Order By: Relevance
“…In contrast to gonococcal infection of HFTOC, where lipopolysaccharides and peptidoglycan monomers released from rapidly dividing gonococci extensively damage both ciliated and nonciliated epithelial cells (Stephens, 1989), infection of HFTOC with C. trachomat u had no overall effect on mucosal architecture or ciliary activity. These data support the results of Hutchinson et al (1979), who found that ciliary activity of fallopian tube mucosa was not diminished by C. trachomatis infection. However, studies of human fallopian tubes removed during active chlamydial salpingitis demonstrate marked inflammation, loss of cilia, oedema and extensive disruption of the mucosal surface.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast to gonococcal infection of HFTOC, where lipopolysaccharides and peptidoglycan monomers released from rapidly dividing gonococci extensively damage both ciliated and nonciliated epithelial cells (Stephens, 1989), infection of HFTOC with C. trachomat u had no overall effect on mucosal architecture or ciliary activity. These data support the results of Hutchinson et al (1979), who found that ciliary activity of fallopian tube mucosa was not diminished by C. trachomatis infection. However, studies of human fallopian tubes removed during active chlamydial salpingitis demonstrate marked inflammation, loss of cilia, oedema and extensive disruption of the mucosal surface.…”
Section: Discussionsupporting
confidence: 82%
“…There are no useful in vitro models to study the possible roles of Chlamydia in infertility. Studies from England have shown that C. trachomatis is capable of infecting human fallopian tube explants in vitro, but the infection does not appear to reduce ciliary action (3). We have confirmed this observation, finding a several-log increase in chlamydial titer in the absence of gross or histopathological damage to human fallopian tube organ cultures.…”
supporting
confidence: 78%
“…Many studies have suggested that most chlamydial disease sequelae are caused by immunopathological reaction (Cooper et al, 1990;Hutchinson et al, 1979;Patton, 1985;Quinn et al, 1992). From the public health perspective, the most troublesome aspect of chlamydial infection is not the infection per se, rather, it is the immunopathological responses that cause major health problems including blindness, infertility, and ectopic pregnancy.…”
Section: Introductionmentioning
confidence: 98%